Bridging the Gap: How Universal Design for Learning Can Transform Biology Education: A Systematic Review - SILVARAJAN, LAVANYA; Kamarudin, Nurzatulshima; Mustakim, Siti Salina (IIUM Journal of Educational Studies, 2025)
Despite significant advancements in pedagogical models, Biology education still relies on the one size-fits-all teaching methods that overlook the diverse needs and strengths of learners. This impacts students with diverse learning needs and abilities, contributing to disengagement and a decline in motivation. The Universal Design for Learning (UDL) framework offers a promising alternative by promoting inclusivity through multiple means of representation, engagement, and expression. This systematic review explores how UDL has been applied in STEM education, particularly Biology, using the updated CAST 2024 UDL checkpoints as an analytical framework. Ten peer-reviewed studies published between 2020 and 2025 were selected and analyzed following PRISMA guidelines. The review identified three recurring themes: choice, variety, and technology. These themes highlight effective strategies such as gamified assessments, digital tools, and differentiated learning tasks that support inclusivity and student engagement. While promising, the findings also reveal gaps in implementation, especially in underused UDL checkpoints related to feedback and self-regulation. This review emphasizes the importance of aligning instructional design with UDL principles to foster inclusive, student-centered Biology education.